Sosialisasi Peraturan Permainan Bola Basket Bagi Siswa Sekolah Menengah Pertama - Suardika, I Kadek; Irawan, Safri (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
The socialization of basketball game rules in junior high schools throughout Gorontalo City was carried out to overcome the main problem of the need for more understanding by students who are active in basketball extracurriculars regarding the latest rule changes. This service aims to convey the latest regulations to junior high school students in Gorontalo City, predominantly male and female students who are active in basketball extracurriculars. The socialization activity lasted for 7 days, from 4 to 10 January 2024, at SMPN 2 Gorontalo City, involving 50 junior high school students throughout Gorontalo City as respondents. Measuring students' understanding of the rules of the basketball game was carried out using a questionnaire, and the results of data analysis showed that 80% of students really understood, 16% understood, and 4% quite understood the rules of the game. Therefore, the participants have a good understanding of aspects such as how to play, the basics of the game, and the rules of the basketball game.